The legality and justifiability of the methods used for monitoring the progress of home-educated children in Finland. Issue 6 (September 2021) - Hartman, Joanna; Huttunen, Rauno
This paper provides an overview of the homeschooling movement in Finland focusing on the methods used to monitor the progress of compulsory education of home-educated children. Although the child's home municipality is obliged to monitor the progress of compulsory education, there are currently no national uniform instructions on how monitoring should take place. Therefore, home-educated children are treated differently depending on where they live. In this article, the authors argue that the current monitoring methods not only decrease the child's motivation to learn but are also inexpedient, illegal and, in many cases, impossible to carry out. The study is based primarily on the qualitative approach, but it combines both qualitative and quantitative methods including surveys, interviews, observation and documents. It is the first empirical research conducted on the monitoring methods of home-educated children in Finland.